Framing Postponement as Continuity: CADS Analysis of ASN Relocation News in DetikNews.com (2024–2025) - Luthfa Sabrina (INJECT (Interdisciplinary Journal of Communication), 2025)
This study analyzes the authoritative narrative construction regarding the postponement of the Civil Servant (ASN) relocation to Indonesia’s New Capital City (IKN) Nusantara. Addressing a gap in the literature that often focuses on social media sentiment, this research investigates the framing strategies employed by the highly influential mainstream source, DetikNews.com. Employing a qualitative Corpus-Assisted Discourse Studies (CADS) design, this research analyzes a corpus of 46 news articles published between August 2024 and March 2025. The methodology integrates quantitative corpus linguistics (Word Frequency, Collocation, and Concordance) with the interpretive lens of Stuart Hall’s Representation Theory and Critical Discourse Analysis (CDA). Key findings reveal that the media consistently frames the postponement as a procedural adjustment (evidenced by collocates such as sementara and kontrak) and an inevitable logistical challenge, rather than a political failure. The study concludes that DetikNews.com engages in discursive legitimation, successfully encoding a Preferred Meaning of project continuity that stabilizes public perception and legitimizes policy continuation.